Kualitas Seorang Gembala Menurut 1 Petrus 5:1-4 - Leo Sidabutar (Voice, 2022)
Elders, shepherd, overseer, bishop, pastor, deacon are terms in the world of Christian leadership. In the context of 1 Peter, the terms elders, shepherds, and overseers refer to the same person. Peter is so serious about giving direction and guidance to them on how they should carry out their pastoral duties and responsibilities. At that time the social situation faced by Christians in the Roman empire was very uncomfortable because they experienced persecution because of their faith and did not want to submit to worship Caesar as God. They stand firm in their faith that only Jesus is the true God and only Jesus they worship. In such situation, the Christian congregations are strengthened and encouraged by Peter to remain firm in holding on to the faith and keep practicing ways of life that are right and in accordance with the teachings of Christ as their great shepherd in all aspects of their lives, including in the internal territory of the congregation. Peter gave instructions and qualities that elders should have in their shepherding as well as those qualities that he saw and imitated in the person of Jesus himself during his life with Jesus. He wants every elder in the Christian community who receives his letter to shepherd people with the qualities and character that Jesus did as the Great Shepherd of all believers.